Knowledge and society : situating sociology and social anthropology - Oommen, T. K., 1937- (New Delhi : Oxford University Press, 2013)
With special reference to India.
Includes bibliographical references (pages 235-248) and indexes.
Keywords: Knowledge, Sociology of; Sociology -- India; Sociology; Ethnology -- India; Ethnology